A Perspective of Continuing Education in a Professional Discipline - Bhattacharyya, G. (Journal of Information and Knowledge, 1999)
Explains the concepts of Profession, and Self-consciousness of a Profession. Establishes the fact that, from the point of view of professionalism, continuing education’is a professional obligation of any profession induding that of library and information work and services. Develops a general reference framework of the essential categories of professional knowledge and skiffs. Claims its application value for designing and continuous revising of the syllabus for any professional course. Shows its usefulness in identifying new topics for organizing continuing education programmes.